Theoretical perspectives of virtual and distance education in Ibero-America - et. al., Lucio Torres-Romero, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The phenomenon of distance education has generated in recent decades a large amount of scientific literature. These contributions, largely of empirical nature, have allowed the elaboration of theoretical proposals. Theories become necessary to guide good practices, at the same time that these nourish theoretical reflections. This paper proposes a theoretical contribution that intends to be global and integrating other previous ones. The proposal is based on considering distance education as a didactic dialogue mediated between the teacher (institution) and the student who, located in a different space from the teacher, learns independently and collaboratively. Dialogue as the basis of quality distance education is analyzed from different dichotomies, dialogues: real-simulated, synchronous-asynchronous, vertical-horizontal, unidirectional-multidirectional, structured-flexible. Therefore, the MOOC (Massive Open Online Course) method is defined as the main variable to analyze according to the theory that has been generated in this regard during the period 2015-2020 in Latin American countries, in order to know the position of different authors with respect to the methodologies of virtual and distance education, as well as the evolution and details of the bibliographical production of the subject under study.